Effect of an Ayurveda antidote Dooshivishari Agada in carboplatin induced myelosuppression in Male Wistar rats - Santosh F. Patil; Vishalaxi V. Shahapurkar; Pukar Khanal (Journal of Ayurveda and Integrative Medicine, 2022)
Background: Carboplatin is one of the common chemotherapeutic agents in the management of various malignant conditions. Myelosuppression remains one of the major adverse effects of it that leads to compromised quality of life and can procrastinate or cease the chemotherapy regimen. Increasing shreds of evidence suggest the role of Complementary and alternate medicine in palliative cancer care. Ayurveda has prescribed Dooshivishari Agada (DVA) as an anti-dote for similar conditions mentioned above which arise out of sub-lethal toxic substances called Dooshivisha (DV). Objective: The present study was carried out to evaluate the role of DVA in myelosuppression among rats. Method: Male Wistar rats weighing 250–275 g were divided into three groups, Group I was administered normal saline and acted as Normal control. Group II and III received a single dose of carboplatin (60 mg/kg through the tail vein) on day one and acted as disease control. Group III received experimental drug DVA 256 mg/kg orally for the next 18 days. Animals were bled on days 0, 3, 6, 9, 12, 15, 18 for hematological analysis. Results: DVA prolonged the nadir time for Hb, RBC, and WBC counts from day 9 to day 12 when compared to the carboplatin group. In terms of Platelet count, there was no significant difference over carboplatin. Group III showed a significant increase in Total reticulocyte count in comparison to group II. Conclusion: Present study showed that DVA may help in delaying the myelosuppression which needs further evaluation.